Implikasi Tafsir Psikologis Surah Yusuf terhadap Pendidikan Akhlak dan Pengendalian Diri: Perspektif Tafsir Al-Azhar Karya Buya Hamka - Angga Suryana (Peradaban Journal of Religion and Society, 2026)
The moral and spiritual challenges faced by Muslim students necessitate the strengthening of moral education that is oriented not only toward cognitive development but also toward character formation and self-control. This study examines the implications of the psychological interpretation of Surah Yusuf for moral education and self-control based on Tafsir Al-Azhar by Buya Hamka. The aim of this research is to analyze the psychological and spiritual values embedded in Surah Yusuf, particularly moral integrity, patience, and self-control, as well as their relevance to contemporary Islamic education. This study employs a library research method using a thematic tafsir approach and narrative analysis of Tafsir Al-Azhar. The findings indicate that Buya Hamka’s interpretation of Surah Yusuf emphasizes the importance of self-control, steadfast faith, and honesty as foundational elements of moral education. These values can be integrated into Islamic educational practices to develop students’ character resilience and adaptability in responding to the challenges of modern life. Tantangan moral dan spiritual yang dihadapi peserta didik Muslim menuntut penguatan pendidikan akhlak yang tidak hanya berorientasi pada aspek kognitif, tetapi juga pada pembentukan karakter dan pengendalian diri. Penelitian ini mengkaji implikasi tafsir psikologis Surah Yusuf terhadap pendidikan akhlak dan pengendalian diri berdasarkan Tafsir Al-Azhar karya Buya Hamka. Tujuan penelitian ini adalah menganalisis nilai-nilai psikologis dan spiritual dalam Surah Yusuf, khususnya integritas moral, kesabaran, dan pengendalian diri, serta relevansinya bagi pendidikan Islam kontemporer. Metode yang digunakan adalah studi pustaka dengan pendekatan tafsir tematik dan analisis naratif terhadap Tafsir Al-Azhar. Hasil kajian menunjukkan bahwa tafsir Buya Hamka terhadap Surah Yusuf menekankan pentingnya pengendalian diri, keteguhan iman, dan kejujuran sebagai fondasi pendidikan akhlak. Nilai-nilai tersebut dapat diintegrasikan ke dalam pembelajaran pendidikan Islam untuk membentuk karakter peserta didik yang kuat dan adaptif terhadap tantangan kehidupan modern.